(untitled) (Environment & Health, 2023)
Objective: To assess the results of monitoring radiation indicators of the state of the environment in the Zaporizhzhia region under the threat of a radiation accident at the Zaporizhzhia NPP in order to make decisions regarding the use of countermeasures. Materials and methods: As a result of the analysis of long-term observations, indicators of radioactivity in the event of a radiation accident were determined. More than 21,000 measurements of the gamma background of the territory were carried out in 13 settlements of the Zaporizhzhia region. The dosimetry method was used to measure the power of the equivalent dose. The radiometric method was used to study the total radioactivity of drinking water from the water supply network. 21 samples were taken. The study of the total beta activity of atmospheric precipitation and settling dust was carried out by the sedimentation method. A total of 34 samples were examined. Results: As a result of the conducted research, it was recorded that the radiation component in the territory of the region did not change – gamma background levels remained within the range of long-term observations of 10-12 μR•h-1. It was established that the total alpha and beta activity of drinking water meets the requirements of the current legislation. The results of the studies of atmospheric sediments and settled dust show that there is no increase in the total beta activity in the atmosphere compared to the average long-term indicator observed in the period before 1986.